Pembelajaran Membaca Al-Qur’an Menggunakan Metode Iqro’ untuk Mengurangi Angka Buta Huruf Al-Qur’an - Rappe; Munawwir, Ahmad; Mappasiara; Syarifuddin, Erlangga; Hasriati (Faculty of Tarbiyah and Teacher Training, 2023)
Society is the pioneer, determinant of progress, and the welfare of a state and nation, therefore the government of a country must pay attention to the welfare of the community, especially the young generation that has just grown up among the community. It is this young generation that will determine the fate of the nation and state in the future, because today's youth are the leaders of the future. Our country, Indonesia, has a lot of diversity in religion, culture, and so on, Indonesia is also a religious country, it can be seen in the ideology of the nation, namely Pancasila, in the first principle which reads